The Effect Of Job Satisfaction On Performance With Job Stress As An Intervening Variabel PT. Supraco Indonesia Duri Riau Branch During The Covid-19 Pandemic - Sri Indrastuti S; Gilang Nugroho; Annisa Aprilia Anggraini (Universitas Dharma Wacana, 2022)
This study aims to determine the effect of job satisfaction on performance with job stress as an intervening variable PT. Supraco Indonesia Duri Riau Branch during the covid-19 pandemis. This study uses a quantitative approach. The population in this was employees of PT. Supraco Indonesia Duri Riau amounted to 42 people and the sample in this study was 40 people. Partial Least Square (PLS) was used to test the hypothesis in this study using by SmartPLS 3.0. The result of this study found that there is a significant positive effect on job satisfaction performance, there is a negative effect of job satisfaction on job stress, there is a negative effect of job stress on performance, and there is an indirect negative effect of job satisfaction performace job stress as an intervening variabel.